Evaluasi Usability dan Perbaikan Rancangan Antarmuka Pengguna Situs Web PT. Lintas Jejak Nusaraya Menggunakan Pendekatan Human Center Design - Nurrachmat Ardhianto; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT. Lintas Jejak Nusaraya is a company engaged in the field of GPS tracking services on vehicles, which utilize the website to provide services to users ranging from information about the current location of the vehicle to record the trip from the vehicle. The problem of branding is almost the same as the business competitors to make PT. Lintas Jejak Nusaraya decided to create a new brand. Interface improvements are needed to strengthen the identity of PT. Lintas Jejak Nusaraya in the new website development. Improved user interface is done using Human Centered Design approach. Aspects of usability used in testing, among others; Efficiency to measure access speed, Effectiveness to measure success rate, and to measure Satisfaction used questionnaire System Usabiliy Scale. A preliminary evaluation is performed on the old interface to explore the problem of the 9 issues used as suggestions for improvements to the proposed prototype and final evaluation done on the prototype to get user feedback from proposed improvements that have been made. From the evaluation result, there is an increasing of satisfaction level which increase from SUS Score 43,5 average in the initial evaluation to SUS Score 71 on final evaluain, increasing the time needed to access PT. Lintas Jejak Nusaraya from an average of 447 seconds to 399 seconds, and the completion rate of 82.8% in the initial evaluation to 97% in the final evaluation.